A wide inter-absorption dual-transmission dual-polarized frequency selective rasorber based on SRRs. Issue 5 (4th July 2022) - Sen, Gobinda; Sharma, Aditi; Ghosh, Saptarshi; Das, Santanu
ABSTRACT: In this letter, a dual-polarized dual-transmission frequency selective rasorber (FSR) geometry is demonstrated. The top layer of the FSR is built of a cross-dipole design loaded with chip resistors for obtaining a wideband absorption. In addition, two different split ring resonator patterns are printed at each side of the substrate connected by metallized vias to achieve two in-band transmission responses. The bottom layer is designed from a slot geometry to exhibit two transmission bands similar to that of the top layer. The overall FSR structure exhibits a −10 dB reflection response ranging from 2.0 GHz to 8.15 GHz (having a fractional bandwidth of 121%), with transmission peaks appearing at 4.2 GHz and 6.2 GHz having insertion losses of 2.3 dB and 2.9 dB, respectively. The unit cell topology is miniaturized with dimensions of 0.1λL ×0.1λL, λL being the free space wavelength at the lowest operating frequency. The proposed FSR also satisfies polarization-insensitive characteristic and angular stability behavior for differentmodes. The working principle behind such wideband absorption and in-band transmission phenomena are analyzed and an equivalent circuit model is presented. A prototype of the proposed FSR is manufactured and measured, confirming the simulated responses.